The children's great texts of the Bible - Hastings, James (C. Scribner's sons, 1920)
I. Genesis to Joshua.--II. Judges to Job.--III. Psalms to Isaiah.--IV. Jeremiah to Matthew.--V. Mark to John.--VI. Acts to Revelation.